The Effect of Leadership Styles and Organizational Culture to Employee Performance Through Job Satisfaction as Intervening Variables (Case Study in IIB Darmajaya) - Anik Irawati (Proceeding International Conference on Information Technology and Business, 2017)
This study aims to find evidence of the influence of leadership style and organizational culture to employee performance through job satisfaction as intervening variable. The sample in this research are employees of IIB Darmajaya that are 122 respondents. Data collection was done through the distribution of questionnaires to the respondents. This research uses Structural Equation Modeling (SEM) path analysis approach. The result of the test using path analysis shows that there are the influence of leadership style to work satisfaction, organizational culture affects to work satisfaction, the influence of leadership style to employee performance, organizational culture affects to employee performance, organizational culture has effect to employee performance, the influence of work satisfaction to employee performance. Based on the test results, they have positive effect to employees performance, from the highest to the lowest effect respectively that are work satisfaction, leadership style, and organizational culture. The results indicate that is needed to improve the leadership style in order to get high work satisfaction and good employee performance. In addition, it also needs to improve the organizational culture to improve high job satisfaction and good performance of employee. The results of this study can be used as material for the management in optimizing employee performance. Employee performance in this case includes organizational culture, leadership style and job satisfaction.Keywords : Leadership Style, Organizational Culture, Job Satisfaction and Employee Performance